Effect Of Albit And Gummi 20 Stimulators On Cotton Yield In Conditions Of Pale Gray Stony Soils (Texas Journal of Agriculture and Biological Sciences, 2024)
Light gray stony soils of Namangan region Albit stimulator 75 ml/t per seed before planting and 40 ml/ha during weeding and Gummi 20 stimulator 1.0 l/t per seed before planting and 1.0-1.5 l/ha during weeding-flowering periods when processed according to standards, the field germination rate of the seed is accelerated by 7.5-9.0%, sprouts germinated 1-2 days earlier and plant height is 7.6-11.7 cm, harvested branches are 1.3-1.8 pieces, total formed pods 1.4-1.8 grains, opening of bolls increased by 3.3-5.0%, additional cotton yield increased by 3.3-5.2 tons/ha.